2015
DOI: 10.3174/ajnr.a4271
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Diffusion-Weighted MRI Parameters and Human Papillomavirus Status in Oropharyngeal Squamous Cell Carcinoma

Abstract: BACKGROUND AND PURPOSE:Patients with human papillomavirus-positive oropharyngeal squamous cell carcinomas have a better survival rate than those with human papillomavirus-negative oropharyngeal squamous cell carcinomas. DWI characterizes biologically relevant tumor features, and the generated ADC may also provide prognostic information. We explored whether human papillomavirus status and ADC values are independent tumor characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 28 publications
2
47
2
Order By: Relevance
“…In agreement with Nakahira et al 12 and Driessen et al, 22 we found that mean ADCs were significantly lower in HPVϩ than in HPVϪ cancers. However, our data are in contradiction to results reported by Schouten et al, 14 who did not find a statistically significant difference between ADCs of both tumor types.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…In agreement with Nakahira et al 12 and Driessen et al, 22 we found that mean ADCs were significantly lower in HPVϩ than in HPVϪ cancers. However, our data are in contradiction to results reported by Schouten et al, 14 who did not find a statistically significant difference between ADCs of both tumor types.…”
Section: Discussioncontrasting
confidence: 57%
“…Recent publications have attempted to determine whether mean ADC values calculated by monoexponential fitting could be used to determine the HPV status in HNSCC. 12,14,22 In contrast to the intravoxel incoherent motion biexponential model, the monoexponential model does not differentiate between molecular movement caused by microperfusion and true diffusion caused by Brownian movement. 23 To obtain a robust fitting, biexponential models require the acquisition of 6 -12 b-values, leading to increased examination time and a higher percentage of motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations